Adult-onset neuronal intranuclear inclusion disease related retinal degeneration: a Chinese case series - Feng, Chaoyi; Chen, Qian; Luan, Xinghua; Sun, Ping; Cao, Yuwen; Wu, Jingying; Wang, Shige; Sun, Xinghuai; Cao, Li; Tian, Guohong (Frontiers in Medicine, 2024)
Purpose To evaluate adult-onset neuronal intranuclear inclusion disease (NIID)-related retinopathy with guanine-guanine-cytosine repeat expansions in NOTCH2NLC. Materials and methods Neuro-ophthalmic evaluations, including best-corrected visual acuity, slit-lamp biomicroscopy, intraocular pressure (IOP), ultrasound biomicroscopy, pupillometry, fundus photography, fundus autofluorescence (FAF), optical coherence tomography (OCT), Humphrey visual field, full-field electroretinography (ERG), and multifocal ERG (mf-ERG) were performed in patients with gene-proven NIID. Results Nine patients (18 eyes) were evaluated, with a median age of 62 years (55–68) and only one man was included in our study. Six patients presented with decreased visual acuity or night blindness, whereas the other three were asymptomatic. The visual acuity was measured from 20/200 to 20/20. Miosis was present in eight patients, four of whom had ciliary process hypertrophy and pronation, and three of whom had shallow anterior chambers. Fundus photography, FAF, and OCT showed consistent structural abnormalities mainly started from peripapillary areas and localized in the outer layer of photoreceptors and inner ganglion cell layer. ERG and mf-ERG also revealed retinal dysfunction in the corresponding regions. Conclusions Patients with NIID showed both structural and functional retinopathies which were unique and different from common cone-rod dystrophy or retinitis pigmentosa. Patients with miosis may have a potential risk of an angle-closure glaucoma attack. Neuro-ophthalmic evaluations is essential for evaluating patients with NIID, even without visual symptom.